2023
DOI: 10.1002/adem.202300053
|View full text |Cite
|
Sign up to set email alerts
|

The Synergistic Effects of Boron and Impression Creep Testing during Paced Controlling of Temperature for P91 Steels

Abstract: This article induces the quadruple knowledge on effects of 100 ppm (P91B) and 22 ppm (P91) boron in as‐received 9Cr steels in normalized and tempered conditions (NT) and impression crept conditions (ICC). Herein, impression creep testing is improved through paced temperature to fast evaluate creep performance. P91B performs the utmost by advancing activation energy and 30% better creep life, leading to same targeted creep life to 574 °C than P91 at 550 °C. Further, it incisively discusses variations in microst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(3 citation statements)
references
References 48 publications
0
3
0
Order By: Relevance
“…Full width at half maximum (FWHM) is directly associated with dislocation density, i.e. peak broadening is due to increase in dislocation density [28,29]. At temperatures between 500 °C-550 °C, the FWHM variation is not pronounced.…”
Section: Type Of Carbide After Temperingmentioning
confidence: 99%
“…Full width at half maximum (FWHM) is directly associated with dislocation density, i.e. peak broadening is due to increase in dislocation density [28,29]. At temperatures between 500 °C-550 °C, the FWHM variation is not pronounced.…”
Section: Type Of Carbide After Temperingmentioning
confidence: 99%
“…Mishra et al 15 believed that boron would improve the strain hardening during high tempering temperature, mainly owing to the delay in lath recovery and structure refinement. The study of Akhtar et al 16 showed that the activation energy and creep life of boron modified P91 steel were improved. The grain boundary hardening was enhanced 17 and the recovery phenomenon was delayed through appropriate post weld heat treatment 18 and addition of boron, which improved the creep strength 19 and suppressed the failure of weld joints in the intercritical heat-affected zone of P91 steel.…”
Section: Introductionmentioning
confidence: 99%
“…The experiments were carried out by machining the composite in Die sinking EDM. Akhtar, & Khajuria (2023) carried out the detailed study of the grain structure and the metrological properties due to the different conditions. The normalized and tempered condition properties were evaluated and the modifications occurring in the grain boundaries were studied in the work.…”
Section: Introductionmentioning
confidence: 99%